The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/s22228630
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Obstructive Sleep Apnea Risk by Using Machine Learning Approaches and Anthropometric Features

Abstract: Obstructive sleep apnea (OSA) is a global health concern and is typically diagnosed using in-laboratory polysomnography (PSG). However, PSG is highly time-consuming and labor-intensive. We, therefore, developed machine learning models based on easily accessed anthropometric features to screen for the risk of moderate to severe and severe OSA. We enrolled 3503 patients from Taiwan and determined their PSG parameters and anthropometric features. Subsequently, we compared the mean values among patients with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This might explain the disparity between their RF model and the current study. Tsai et al ( 2022 ) employed waist circumference, neck circumference, BMI, and visceral fat level to establish risk models for predicting moderate to severe OSA using LR, k-nearest neighbor, Bayesian, RF, SVM, and XGBoost. The RF model, applied to the moderate-severe category, demonstrated an accuracy of 84.74% and an AUC of 90.41%, highlighting its robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the disparity between their RF model and the current study. Tsai et al ( 2022 ) employed waist circumference, neck circumference, BMI, and visceral fat level to establish risk models for predicting moderate to severe OSA using LR, k-nearest neighbor, Bayesian, RF, SVM, and XGBoost. The RF model, applied to the moderate-severe category, demonstrated an accuracy of 84.74% and an AUC of 90.41%, highlighting its robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings, we observed significant associations between the visceral fat level and trunk-to-limb fat ratio in the low-ArTH OSA group. A study reported that visceral fat was a predominant indicator in the evaluation of the AHI level and nocturnal hypoxemia severity [ 38 ]. Another study reported that excess visceral fat can cause severe hypoxemia during sleep and an increased risk of metabolic syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, on the basis of our literature review, six machine learning approaches, including random forest (RF), extreme gradient boosting (XGBoost), k-nearest neighbor (kNN), support vector machine (SVM), naive Bayes (NB), and logistic regression (LR), were recruited to establish screening models for two different OSA severity risk levels. 27 , 28 Figure 2 demonstrates the flowchart of developing the models. Initially, all of the collected data were integrated as a total dataset and subsequently independently separated into training and test datasets at an 80% to 20% ratio.…”
Section: Methodsmentioning
confidence: 99%